2017
DOI: 10.1038/s41598-017-04334-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Photoacoustic Imaging of Anterior Ocular Vasculature: A Random Sample Consensus Approach

Abstract: Visualizing ocular vasculature is important in clinical ophthalmology because ocular circulation abnormalities are early signs of ocular diseases. Photoacoustic microscopy (PAM) images the ocular vasculature without using exogenous contrast agents, avoiding associated side effects. Moreover, 3D PAM images can be useful in understanding vessel-related eye disease. However, the complex structure of the multi-layered vessels still present challenges in evaluating ocular vasculature. In this study, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…Tight optical focusing will further improve the lateral resolution for PAM and resolution up to 0.32 µm has been reported using OR-PAM [13]. The imaging depth in OR-PAM is limited by optical transport mean free path (~1 mm inside the biological tissue) [14][15][16]. In OR-PAM, the optical delivery is mainly through a SM fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Tight optical focusing will further improve the lateral resolution for PAM and resolution up to 0.32 µm has been reported using OR-PAM [13]. The imaging depth in OR-PAM is limited by optical transport mean free path (~1 mm inside the biological tissue) [14][15][16]. In OR-PAM, the optical delivery is mainly through a SM fiber.…”
Section: Introductionmentioning
confidence: 99%
“…However, the imaging depth is limited (700 μm) and the depth of variation of corneal vessels can be more than 1.4 mm owing to the curvature of the mouse cornea. Jeon et al [17] have demonstrated a new method to evaluate blood circulation in the eye by combining in vivo PAM imaging. By using a machine learning algorithm, random sample consensus algorithm (RANSAC), they could have visualize the PA anterior ocular vasculature image and demonstrate layer-by-layer analysis of corneal neovascularization on a mouse eye (Figure 3c-e).…”
Section: Corneal Neovascularizationmentioning
confidence: 99%
“…Based on system designs to yield different resolutions and penetration depth, PAM can be classified into optical-resolution (OR) and acoustic-resolution (AR) PAM. OR-PAM uses tight optical focusing 8,9 to achieve a high lateral resolution of 0.32 μm and penetration depth of up to 1 mm. [10][11][12] AR-PAM employs tight acoustic focusing and weak optical focusing to achieve imaging depth of up to 3 mm (>optical mean free path of 1 mm) with a lateral resolution of 45 μm at 570 nm.…”
Section: Introductionmentioning
confidence: 99%